Investigating The Influence of Tooth Loss on Salivary Flow Rate: A Community-Based Report - Aida Fadhilla Darwis; Wilda Hafny Lubis; Pocut Astari; Nasya Ayu Viandini; Jesslin Priskila (TALENTA, 2025)
Increasing age has been reported to be associated with a higher prevalence of tooth loss and a greater risk of decreased salivary flow rate. This is because physiological aging affects both the dentition and salivary gland function. Degenerative changes in the oral tissues has also been shown to reduce glandular efficiency. Therefore, this study aims to analyze salivary flow rate based on the number of missing teeth in the elderly. The current study is part of a Community Service activity conducted at Martubung Public Health Center, Medan, in 2023. The sample population included elderly individuals aged ≥60 years who regularly participated in elderly posyandu (integrated health service posts) activities, with a total sample of 50 participants consisting of 38 females and 12 males. For each participant, the number of remaining teeth was counted, followed by the collection and measurement of both unstimulated and stimulated salivary flow rate for 5 minutes. The data obtained were then analyzed using the Pearson test. The results showed that the group with 15–24 missing teeth had the highest number of elderly individuals, totaling 21. In addition, unstimulated and stimulated salivary flow rate were highest in the group with 1–14 missing teeth, with mean values of 1.79±0.90 ml/min and 2.73±1.39 ml/min, respectively. The Pearson test showed a significance value of 0.05. Based on the analysis results, a higher salivary flow rate is associated with fewer missing teeth among the elderly. Key words: number of teeth, saliva flow rate, elderly